EFFECT OF QUADRICEPS ISOMETRIC EXERCISE ON REDUCING PAIN IN ELDERLY COMMUNITIES WITH KNEE OSTEOARTHRITIS - Basuki, Rochman; Dewi, Novita Sari; Rizqulloh, Dzaky Azmi; Pranata, Satriya (Journal of Vocational Health Studies, 2024)
Background: It is necessary to make innovations that make it easier for osteoarthritis sufferers to do exercises independently at home. Patients can apply proper self-management, such as doing pain-reducing quadriceps muscle exercises. Purpose: This study aimed to analyze the effect of quadriceps isometrics on pain intensity in the elderly community with knee osteoarthritis. Method: This study uses a quasi-experimental design with pre and post-test control group design. The sample was selected using a consecutive sampling technique, which consisted of 30 older people divided into 15 older people for each intervention and control group. The intervention group sample was given a treatment of quadriceps isometric for weeks with a frequency of twice a week, and then the control group was given education. The analysis used is a statistical test paired sample T-test and an independent T-test. Result: The paired sample statistics obtained the average pain result in the pre-intervention category with a scale of 6.2, while after the intervention, it was 5.2with a p-value < 0.05. In the paired sample statistics, the average pain result in the category before education was 7.28, while after education, it was 8.03 with a p-value < 0.05. In the independent T-test for the intervention and control groups, the results obtained were a p-value of 0.039 < 0.05. Conclusion: There was a significant difference between the average intervention and control groups of quadriceps isometric exercise in reducing pain intensity in elderly patients.